2023
DOI: 10.1021/acsami.3c02251
|View full text |Cite
|
Sign up to set email alerts
|

Flame-Retardant and Self-Healing Waterborne Polyurethane Based on Organic Selenium

Abstract: Waterborne polyurethane has drawn extensive attention due to its environmental friendliness and is widely used in many areas. However, it is still a great challenge to synthesize waterborne polyurethanes with flame retardancy and fast roomtemperature self-healing ability, along with excellent mechanical performance and emulsion stability due to the mutually contradictory nature of these properties. Herein, waterborne polyurethanes containing organic selenium (SWPU-x) from 0.67 to 3.28 wt % were synthesized, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…However, the weak dynamic nature of the internal crystallinity, entanglement, and strong covalent bonds often hinder the migration ability of polymer chains, making it difficult to achieve self-repairing performance. In recent years, there has been extensive research and reporting on incorporating reversible bonds into polymer chains to confer repairability to materials. These include covalent reversible bonds, such as disulfide bonds, , Diels–Alder (D–A) reactions, , boronic ester bonds, , acyl hydrazone bonds, and diselenide bonds, as well as noncovalent reversible bonds, such as hydrogen bonds, coordination bonds, π–π stacking, ionic bonds, and others . Among them, the hydrogen bond is a type of dipole–dipole interaction, and its strength depends on the nature of the donor and acceptor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the weak dynamic nature of the internal crystallinity, entanglement, and strong covalent bonds often hinder the migration ability of polymer chains, making it difficult to achieve self-repairing performance. In recent years, there has been extensive research and reporting on incorporating reversible bonds into polymer chains to confer repairability to materials. These include covalent reversible bonds, such as disulfide bonds, , Diels–Alder (D–A) reactions, , boronic ester bonds, , acyl hydrazone bonds, and diselenide bonds, as well as noncovalent reversible bonds, such as hydrogen bonds, coordination bonds, π–π stacking, ionic bonds, and others . Among them, the hydrogen bond is a type of dipole–dipole interaction, and its strength depends on the nature of the donor and acceptor.…”
Section: Introductionmentioning
confidence: 99%
“…10−13 In recent years, there has been extensive research and reporting on incorporating reversible bonds into polymer chains to confer repairability to materials. These include covalent reversible bonds, such as disulfide bonds, 14,15 T h i s c o n t e n t i s Diels−Alder (D−A) reactions, 16,17 boronic ester bonds, 18,19 acyl hydrazone bonds, 20 and diselenide bonds, 21 as well as noncovalent reversible bonds, such as hydrogen bonds, 22 coordination bonds, 23 π−π stacking, 24−26 ionic bonds, and others. 27 Among them, the hydrogen bond is a type of dipole− dipole interaction, and its strength depends on the nature of the donor and acceptor.…”
Section: Introductionmentioning
confidence: 99%
“…These bonds should have the capability to undergo easy breakage and reformation, facilitating the recovery of the material’s network structure. Ionic interactions, Diels–Alder reactions, oxime bonds, diselenide bonds, B–O bonds, disulfide bonds, and Schiff bases, which are dynamic covalent bonds, have been commonly employed in formulating healable and recyclable SHWPU. Again, certain research studies have suggested that incorporating hydrogen bonds can enhance the mechanical strength of self-healing polyurethane elastomers .…”
Section: Introductionmentioning
confidence: 99%
“…Visible light can be employed for a wide range of compounds, including small diselenides and polymers. , Due to the low bond energy of the Se–Se bond, visible light can easily break the diselenide bond without the need for a catalyst, making diselenide metathesis compatible with biological systems. This property of Se–Se bonds has paved the way for the development of dynamic systems with properties such as self-healing, shape memory, and so on …”
Section: Introductionmentioning
confidence: 99%